A sucrose non‐fermenting‐1‐related protein kinase‐1 gene, IbSnRK1, improves starch content, composition, granule size, degree of crystallinity and gelatinization in transgenic sweet potato. Issue 1 (29th May 2018) - Ren, Zhitong; He, Shaozhen; Zhao, Ning; Zhai, Hong; Liu, Qingchang
Summary: Sucrose non‐fermenting‐1‐related protein kinase‐1 (SnRK1) is an essential energy‐sensing regulator and plays a key role in the global control of carbohydrate metabolism. The SnRK1 gene has been found to increase starch accumulation in several plant species. However, its roles in improving starch quality have not been reported to date. In this study, we found that the IbSnRK1 gene was highly expressed in the storage roots of sweet potato and strongly induced by exogenous sucrose. Its expression followed the circandian rhythm. Its overexpression not only increased starch content, but also decreased proportion of amylose, enlarged granule size and improved degree of crystallinity and gelatinization in transgenic sweet potato, which revealed, for the first time, the important roles of SnRK1 in improving starch quality of plants. The genes involved in starch biosynthesis pathway were systematically up‐regulated, and the content of ADP‐glucose as an important precursor for starch biosynthesis and the activities of key enzymes were significantly increased in transgenic sweet potato. These findings indicate that IbSnRK1 improves starch content and quality through systematical up‐regulation of the genes and the increase in key enzyme activities involved in starch biosynthesis pathway in transgenic sweet potato. This gene has the potential to improve starch content and quality in sweet potato and other plants.